Regulating the space and the future of the European space policy - Pădureanu, Mihaela-Adriana (European Institute of Romania, 2022)
In this working paper we present and discuss the main directions in the development of the outer space policy with a special focus on the relation between the European countries. The strategic importance of the outer space has been acknowledged during the Cold War and has stayed that way ever since. At the same time, as the progress in the economic area has required more advanced and efficient tools for communication and transportation, the technological development of the outer space instruments had to offer solutions and innovation for answering the need of the commercial sector. The opening of the space sector to other (non)state actors has accelerated in the last years. In this analysis we focused on the European approach to this domain and to the way in which the European Union has started and developed its role in this sector. The paper offers a few policy recommendations for the national and European levels of action aiming to highlight the relevance of this activity and to straighten the coherence of a common approach in the outer space.
10419/281082
Keywords: Graue Literatur; Space; european space policy; rules; United Nations